Improving Students’ Reading Comprehension by Using Cooperative Integrated Reading and Composition (CIRC) Technique - Ester Julinda Simarmata (Departement of Mathematics Education, 2023)
The objective of the study is to investigate whether the application of Cooperative Integrated Reading and Composition (CIRC) Technique significantly improves the students’ achievement in reading narrative text. This study was conducted by using classroom action research. The subject of this research was the student class X IPA which consisted of 15 students. The research was conducted in two cycles. The first cycle consisted of three meetings and the second cycle consisted of three meetings. The instruments for collecting data were students’ score test, observation sheet and interview sheet. Based on analysis, students’ achievement is improved in every cycle test of reading narrative text. In the first cycle show that the level of students’ reading comprehension in narrative text was 69,33. In the second cycles show that the level of students’ ability in reading comprehension of narrative text can be improved by Cooperative Integrated Reading and Composition (CIRC) Technique. The student were more active, motivated, cooperated and enthusiastic working in group. It means that most students got the points to comprehend reading text after applied the Cooperative Integrated Reading and Composition (CIRC) Technique.